Short-term variability of total column ozone from the Dobson spectrophotometer measurements at Belsk, Poland, in the period 23 March 1963–31 December 2019. Issue 1 (1st January 2021) - Krzyścin, J. W.; Rajewska-Więch, B.; Borkowski, J.
Abstract: Total column ozone (TCO) monitoring with the Dobson spectrophotometer no. 84 have been carried out at Belsk (51°50′, 20°47′), Poland, since 23 March 1963. TCO observations were made for various combinations of double wavelength pairs (AD, CD, CC′) and instrument settings (direct Sun, zenith blue, and zenith cloudy). In total, results of 115, 736 manual observations were recorded in the period 1963–2019. The following metrics of the intraday TCO variability are examined: standard deviation divided by the mean value and the difference between the daily maximum and minimum divided by the mean value. The mean value, standard deviation, and 5th–95th percentile range for the intraday changes of the metrics are 1.6%, 0.8%, 2.5% and 4.3%, 2.3%, 7.3%, , respectively. To examine interday TCO variability, one-day changes of the metrics and the daily mean TCO are analysed. The corresponding statistics for one-day change of TCO are −0.2%, 6.9%, 22.6%. The short-term TCO variability changed only slightly (if ever) since the beginning of the ozone observations at Belsk.